MOTIVASI PETERNAK PLASMA AYAM BROILER DALAM BERMITRA DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (STUDI KASUS PT. GEMILANG UNGGAS PRIMA) - Purbata, Ardi Gustri; ', Cepriadi; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is knowing the pattern of partnerships run by PT. Gemilang Unggas Prima, also to know the motivation of broiler chicken breedersplasma in partnering, and partnership problems in broiler chickens in Kampar Kiri Tengah District, Kampar Regency. This type research is descriptive quantitative with using quantitative and qualitative data, collecting data is done with interviewing. Data analysis which is used is descriptive statistic with descriptive analysis and factor analysis. Descriptive analysis of patterns of partnerships demonstrate a partnership which is run by PT. Gemilang Unggas Prima is plasma system, with the system and partner acceptance procedures are clearly specified in the letter of agreement. In addition, the contract price of feed, DOC, and live chicken price agreed in the contract signed by each production period. The result of this research show 7 (seven) variable fill requirement so that it results 2 (two) form motivation namely basic and supporting motivation. Basic motivations which support breeder to determine partner are variable material needs, rewards, and achievements. Basic motivations have real influence of breeder to determine partner. Supporting motivations consist of variable jobs, company policies, supervision, and awards. Supporting motivations have smaller function than basic motivation. Descriptive analysis of the problems of partnership shows that the dominant problem is the contract unilaterally, price contract of livestock production facilities and production is determined unilaterally,deposit/guarantee aggravating plasma farmers,lack of clarity in the quality standards of livestock production facilities is given, and absence of supporting institutions. Keywords: Broiler, Motivation of breeder, Parthership